Enhanced Degradability of Mg-2Gd Alloy by Alloying Cu. Issue 7 (6th July 2021) - Zhong, Shiyu; Zhang, Dingfei; Xu, Junyao; Zhou, Jie; Zhao, Yang; Feng, Jingkai; Wang, Yongqin; Jiang, Bin; Pan, Fusheng
Abstract : To obtain alloys with both high degradability and plasticity used in the petroleum industry, 0.25, 0.5, 0.75 and 1.0 wt.% Cu were added into Mg-2Gd alloy. With Cu addition, finer grain size, precipitation of Mg2 Cu, and variations of crystal orientation were observed. Regardless of the good mechanical properties gained by alloying Cu, the degradation rate was obviously increased in this study. The corrosion rate and I corr of Mg-2Gd were 13.0 ± 0.1 mm·y −1 and 1.04 × 10 −4 A·cm −2, respectively, while those value of Mg-2Gd-1Cu increased to 226.4 ± 6.1 mm·y −1 and 3.42 × 10 −4 A·cm −2, respectively. We confirmed by scanning Kelvin probe force microscopy and scanning electron microscope with electron backscatter diffraction detector that profuse second phases (mainly Mg2 Cu), refinement of grain size, and weakened rare earth texture contributed to the lower corrosion resistance.